Constitutive modeling of polycarbonate during high strain rate deformation. Issue 4 (19th September 2012) - Safari, Keivan H.; Zamani, Jamal; Ferreira, Fernando J.; Guedes, Rui M.
Abstract A constitutive model is presented for large strain deformation of polycarbonate (PC) at high strain rates (above 102 s−1). The proposed model considers the primary process (α) and the two secondary rate‐activated processes (β and γ). It is shown that the secondary transitions in the material affect the yield and post yield behavior of the material at high strain rates. The constitutive model has been implemented numerically into a commercial finite element code through a user material subroutine. The experimental results, obtained using a split Hopkinson pressure bar, are supported by dynamic mechanical thermal analysis (DMTA) and DSR (Decompose/Shift/Reconstruct) method. These are employed to gain understanding of the material transitions, and to further the linkages between material viscoelastic, yield, and stress–strain behavior. Comparison of model predictions with experimental data demonstrates the ability of model to capture the characteristic features of stress–strain curve of the material such as initial linear elasticity, global yield, strain softening, and strain hardening at very high strain rates (up to 10, 000 s−1). POLYM. ENG. SCI. 2013. © 2012 Society of Plastics Engineers